The s-d exchange model as the underlying mechanism of magnetoresistance in ZnO doped with alkali metals. (7th June 2019) - Zapata, C; Nieva, G; Ferreyra, J M; Villafuerte, M; Lanoël, L; Bridoux, G
Abstract: High field magnetoresistance has been studied in epitaxial n -type ZnO:Na and ZnO:Li thin films in a temperature range between 4 K and 150 K. The resulting negative magnetoresistance can be well fitted using a semiempirical model of Khosla and Fischer based on third order contributions to the s - d exchange Hamiltonian. The parameters obtained from this model were carefully analyzed. One of these parameters is related to a ratio between electron mobilities at zero field (a non-exchange scattering mobility and an exchange or spin dependent one ). From Hall effect measurements was obtained, displaying a weak temperature dependence in accordance with highly n -doped ZnO while the extracted exhibits an anomalous T -dependence. On the other hand, our magnetoresistance data cannot be properly fitted using Kawabata's expression based on a weak-localization model.